Faktor yang Berhubungan dengan Fatigue Pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis di RS H.L. Manambai Abdulkadir Sumbawa - Andri Juwita Pranado; Evi Gustia Kesuma; Lina Dewi Anggraeni (Malahayati Nursing Journal, 2026)
ABSTRACT Fatigue affects 60 to 80 percent of patients with chronic kidney disease undergoing hemodialysis. A local preliminary survey showed that 60 percent of patients experienced severe fatigue. However, studies integrating physiological, psychological, clinical, and healthcare access factors within a single analytical model remain limited. Factors associated with fatigue and the most dominant factor among patients with chronic kidney disease undergoing hemodialysis were identified in this study. This quantitative observational analytic study employed a cross sectional approach. From a population of 69 patients, 59 respondents were selected using the Slovin formula and purposive sampling. Data were collected between 4 and 18 June 2026 using the FACIT-F, the HARS, and a medical record observation form. Data were analyzed using the Chi Square test and binary logistic regression with SPSS. The largest proportion of respondents experienced severe fatigue (35.6 percent). Bivariate analysis showed that hemoglobin level (p = 0.003; OR = 5.556), comorbidities (p = 0.001; OR = 6.111), anxiety (p = 0.028; OR = 3.429), and duration of hemodialysis (p = 0.046; OR = 2.923) were significantly associated with fatigue. Hemodialysis frequency (p = 0.250) and distance to the facility (p = 0.902) were not significantly associated. Multivariate analysis showed that hemoglobin level was the most dominant factor (AOR = 13.534; p = 0.002), followed by comorbidities (AOR = 11.759; p = 0.002) and anxiety (AOR = 5.183; p = 0.034). Duration of hemodialysis was no longer significant after adjustment (p = 0.078). Fatigue assessment in hemodialysis units should be integrated with hematological monitoring, comorbidity identification, and psychological screening, with anemia control as the primary priority. Keywords: Anxiety, Chronic Kidney Disease, Fatigue, Hemodialysis, Hemoglobin Level. ABSTRAK Fatigue dialami 60 sampai 80 persen pasien gagal ginjal kronik yang menjalani hemodialisis. Survei awal setempat menunjukkan 60 persen pasien mengalami fatigue berat. Namun, kajian yang mengintegrasikan faktor fisiologis, psikologis, klinis, dan akses layanan dalam satu model analisis masih terbatas. Diketahuinya faktor yang berhubungan dengan fatigue serta faktor paling dominan pada pasien gagal ginjal kronik yang menjalani hemodialisis diidentifikasi melalui penelitian ini. Penelitian kuantitatif analitik observasional ini menggunakan pendekatan potong lintang. Dari populasi 69 pasien, sebanyak 59 responden dipilih menggunakan rumus Slovin dan teknik purposive sampling. Data dikumpulkan pada 4 sampai 18 Juni 2026 menggunakan FACIT-F, HARS, dan lembar observasi rekam medis. Analisis dilakukan menggunakan uji Chi Square dan regresi logistik biner dengan SPSS. Proporsi terbesar responden mengalami fatigue berat sebesar 35,6 persen. Analisis bivariat menunjukkan kadar hemoglobin (p = 0,003; OR = 5,556), penyakit penyerta (p = 0,001; OR = 6,111), kecemasan (p = 0,028; OR = 3,429), dan lama hemodialisis (p = 0,046; OR = 2,923) berhubungan signifikan dengan fatigue. Frekuensi hemodialisis (p = 0,250) dan jarak ke fasilitas (p = 0,902) tidak berhubungan signifikan. Analisis multivariat menunjukkan kadar hemoglobin merupakan faktor paling dominan (AOR = 13,534; p = 0,002), diikuti penyakit penyerta (AOR = 11,759; p = 0,002) dan kecemasan (AOR = 5,183; p = 0,034). Lama hemodialisis tidak lagi signifikan setelah dikontrol (p = 0,078). Pengkajian fatigue di unit hemodialisis perlu diintegrasikan dengan pemantauan status hematologis, identifikasi komorbiditas, dan skrining psikologis, dengan pengendalian anemia sebagai prioritas utama. Kata Kunci: Fatigue, Gagal Ginjal Kronik, Hemodialisis, Kadar Hemoglobin, Kecemasan.